Strategi Efektif untuk Sukses dalam Karier sebagai Pendidik Luar Sekolah - Dira Meri Andika (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This article discusses effective strategies for building a successful career as an out-of-school educator. This article identifies several important qualities and skills that successful out-of-school educators should possess, such as a passion for the outdoors, the ability to teach and mentor others, and good communication skills. This article also discusses the importance of networking with other professionals in the field of out-of-school education and engaging in ongoing professional development.